PENERAPAN PROJECT BASED LEARNING BERBASIS KEARIFAN LOKAL DALAM PEMBELAJARAN EKONOMI UNTUK MENUMBUHKAN JIWA KEWIRAUSAHAAN SISWA SMA - Sukri, Marsuti; Tuandali, Jenni Greis; Zulaeha, Ode (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
This study aims to analyze the implementation of the Project Based Learning (PjBL) model based on local wisdom in Economics learning as a strategy to foster entrepreneurial spirit among classes (X IPS) Muhamaddiyah high school students . The background of this research stems from the need for education that not only develops students’ understanding of economic concepts but also builds creative, innovative, and opportunity-oriented character. Integrating local wisdom into PjBL is believed to enrich students’ learning experiences through the utilization of cultural potential and local resources. This research employs a qualitative descriptive approach involving Economics teachers and students as research subjects. Data were collected through observations, interviews, and documentation throughout the learning process. The findings show that PjBL based on local wisdom can enhance students’ active engagement in designing, developing, and presenting products or projects with economic value. Furthermore, students demonstrated improvements in critical thinking, creativity, responsibility, and collaborative skills. This model also encourages students to better recognize regional potential and develop business ideas rooted in local traditions, making learning more relevant to real-life contexts. The implementation of PjBL provides meaningful and contextual learning experiences for students. Thus, the use of PjBL based on local wisdom can serve as an alternative instructional strategy in Economics learning to foster entrepreneurial spirit from an early age.